Double-layer all-solid-state electrolyte membrane and preparation method and application thereof

The double-layer all-solid electrolyte membrane is prepared by dry-wet composite. Combined with the advantages of the dry-halogen solid electrolyte membrane and the wet sulfide solid electrolyte membrane, it solves the problems of narrow voltage windows and instability to metal lithium in the prior art, and realizes a low-cost and high-performance all-solid battery electrolyte membrane.

CN119725691APending Publication Date: 2025-03-28上海科源固能新能源科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411913559.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing sulfide solid electrolyte membrane or halide solid electrolyte membrane have problems such as narrow voltage window, unstable metal lithium, high material cost and high technical difficulty, resulting in limited commercialization of all-solid lithium batteries.

Method used

A double-layer all-solid electrolyte membrane was prepared by dry-wet-process composite, and a halide solid electrolyte membrane was prepared as the main body through a dry-process process, and a sulfide solid electrolyte membrane prepared by wet was coated on one side to form a double-layer structure.

Benefits of technology

It realizes a low-cost, low-technical difficulty and high-voltage resistance all-solid electrolyte membrane, avoiding the problem that PTFE on the dry side is easily reduced by metal lithium and the unstableness of halide solid electrolyte to lithium, and improving the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725691A_ABST
    Figure CN119725691A_ABST
Patent Text Reader

Abstract

The invention relates to a double-layer all-solid-state electrolyte membrane as well as a preparation method and application thereof. Preparing a first solid electrolyte membrane on the base material by adopting a dry process; and coating one side of the first solid-state electrolyte membrane with the second solid-state electrolyte slurry by adopting a wet process, drying, rolling and compounding to obtain the double-layer all-solid-state electrolyte membrane. Compared with the prior art, the problem of narrow electrochemical window of the sulfide solid electrolyte is solved. The dry-wet method composite solid electrolyte membrane is low in cost and low in technical difficulty, has the advantages of a sulfide solid electrolyte and a halide solid electrolyte, and abandons the respective defects of the sulfide solid electrolyte and the halide solid electrolyte; and meanwhile, the advantages of a dry process and a wet process are integrated, and the preparation method is a novel all-solid-state electrolyte membrane preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state battery materials, and in particular relates to a double-layer all-solid-state electrolyte membrane and a preparation method and application thereof. Background Art

[0002] In recent years, the technology of lithium batteries has developed rapidly. Liquid lithium batteries use liquid electrolytes, which may spontaneously combust when used. Especially in the current situation where the energy density of lithium batteries is getting higher and higher, the safety hazards of liquid lithium batteries are increasingly concerned by people. In order to eliminate this safety hazard, all-solid-state lithium batteries came into being. All-solid-state lithium batteries currently generally use sulfide solid electrolytes or halide solid electrolytes with high ion conductivity. However, the film-making technology of sulfide solid electrolytes is difficult, the material cost is high, and it is unstable to high-voltage materials. The film-making technology of halide solid electrolytes is also difficult and unstable to metallic lithium. The difficulty in modeling, mass production and commercialization of sulfide solid electrolytes or halide solid electrolyte materials has led to stagnation in the progress of all-solid-state lithium batteries. How to prepare low-cost, high-voltage-resistant, and low-tech all-solid-state electrolyte membranes is crucial to the development of all-solid-state batteries. Summary of the invention

[0003] Existing sulfide solid electrolyte membranes or halide solid electrolyte membranes generally have problems such as narrow voltage window, instability to metallic lithium, high material cost, high technical difficulty, etc. Based on this, the present invention provides a double-layer all-solid electrolyte membrane and its preparation method and application.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] The present invention first provides a method for preparing a double-layer all-solid electrolyte membrane, comprising the following steps:

[0006] 1) preparing a first solid electrolyte membrane on a substrate by a dry process;

[0007] 2) A wet process is used to coat a second solid electrolyte slurry on one side of the first solid electrolyte membrane, dry it, and roll-press it to obtain a double-layer all-solid electrolyte membrane.

[0008] In one embodiment of the present invention, the method for preparing the first solid electrolyte membrane on the substrate using a dry process is:

[0009] The first solid electrolyte powder and the binder are fiberized, and the fiberized mixture is rolled into a base film by a first-stage roller press, and then heated and rolled to a target thickness by a second-stage roller press to obtain a first solid electrolyte membrane, and then the first solid electrolyte membrane is attached to the substrate by a third-stage roller press so that it has a certain tensile strength in subsequent processes.

[0010] In one embodiment of the present invention, the mass ratio of the first solid electrolyte powder to the binder is 95:5 to 99.9:0.1, preferably 99.5:0.5.

[0011] In one embodiment of the present invention, the first solid electrolyte is selected as a sulfide solid electrolyte, a halide solid electrolyte or an oxide solid electrolyte, preferably a halide solid electrolyte, the sulfide solid electrolyte is selected from LSPC, LGPS, etc.; the halide solid electrolyte is selected from LZC, LIC, LYC, etc.; the oxide solid electrolyte is selected from LLZTO, LLTO, LAGP, etc.

[0012] Preferably, the first solid electrolyte is selected as LZC.

[0013] In one embodiment of the present invention, the binder is selected from any one or more combinations of PTFE, cellulose mesh, nylon mesh or Kevlar mesh. Preferably, the binder is selected from PTFE.

[0014] In one embodiment of the present invention, the fiberization treatment is carried out by using a combination of one or more of a high-speed planetary mixer, a three-dimensional mixer or a drum mixer.

[0015] In one embodiment of the present invention, the heating temperature of the two-stage roller press is 45°C-130°C, preferably 90°C.

[0016] In one embodiment of the present invention, the thickness of the first solid electrolyte membrane is 5um-45um, preferably 10um.

[0017] In one embodiment of the present invention, the substrate is selected from one of PET film, copper foil, aluminum foil or aluminum-plastic film, preferably PET film.

[0018] In one embodiment of the present invention, a wet process is used to coat a second solid electrolyte slurry on one side of a first solid electrolyte membrane, dry it, and roll-press it to obtain a double-layer all-solid electrolyte membrane. The specific method is:

[0019] A second solid electrolyte slurry is prepared, and the second solid electrolyte and a binder are added to a low-polarity solvent, stirred and dispersed, and the prepared second solid electrolyte slurry is coated on the first solid electrolyte membrane through a die head, and after baking, it is rolled and compounded by a 4-stage roller press to finally obtain a dry-wet composite solid electrolyte membrane, that is, a double-layer all-solid-state electrolyte membrane.

[0020] In one embodiment of the present invention, the mass ratio of the second solid electrolyte to the binder is 90:10 to 99.5:0.5, preferably 98:2.

[0021] In one embodiment of the present invention, the second solid electrolyte is selected from a sulfide solid electrolyte, a halide solid electrolyte or an oxide solid electrolyte, preferably a sulfide solid electrolyte, the sulfide solid electrolyte is selected from LSPC, LGPS, etc.; the halide solid electrolyte is selected from LZC, LIC, LYC, etc.; the oxide solid electrolyte is selected from LLZTO, LLTO, LAGP, etc.

[0022] Preferably, the second solid electrolyte is selected as LPSC.

[0023] In one embodiment of the present invention, the binder is selected from one or more of PVDF, nitrile rubber, polyvinylidene fluoride, butadiene rubber, polyvinyl alcohol butyral, styrene ethylene butylene styrene copolymer, hydrogenated nitrile rubber, polyisobutylene, carboxymethyl cellulose, ethyl cellulose or polyvinyl acetate. Preferably, the binder is selected from PVDF.

[0024] In one embodiment of the present invention, the low polarity solvent is selected from one or more of isobutyl isobutyrate, toluene, xylene, chlorobenzene, n-hexane, cyclohexane, heptane, ethyl propionate, dimethyl carbonate or dibutyl ether. Preferably, the low polarity solvent is selected from isobutyl isobutyrate.

[0025] In one embodiment of the present invention, the solid content of the second solid electrolyte slurry is 15wt%-75wt%, preferably 45wt%.

[0026] In one embodiment of the present invention, the baking temperature is 45°C-130°C, preferably 90°C.

[0027] In one embodiment of the present invention, the pressure of the 4-stage roller press is 5t-30t, preferably 10t.

[0028] In one embodiment of the present invention, preferably, the method for preparing a double-layer all-solid electrolyte membrane comprises the following steps:

[0029] 1) A halide solid electrolyte membrane is prepared on a substrate using a dry process;

[0030] 2) A wet-blowing process is used to coat a sulfide solid electrolyte slurry on one side of the halide solid electrolyte membrane, which is then dried and rolled to obtain a double-layer all-solid electrolyte membrane.

[0031] The present invention further provides a double-layer all-solid-state electrolyte membrane prepared based on the above method, comprising a substrate, a first solid-state electrolyte layer formed on the substrate, and a second solid-state electrolyte layer formed on the first solid-state electrolyte layer.

[0032] Preferably, in the double-layer all-solid-state electrolyte membrane, the first solid-state electrolyte layer is selected as a halide solid-state electrolyte layer, and the second solid-state electrolyte layer is selected as a sulfide solid-state electrolyte layer.

[0033] The present invention further provides the use of a double-layer all-solid-state electrolyte membrane prepared based on the above method in the preparation of a solid-state battery.

[0034] The present invention further provides a solid-state battery comprising the double-layer all-solid-state electrolyte membrane.

[0035] In one embodiment of the present invention, in a solid-state battery, a halide solid electrolyte membrane formed by a dry process faces the positive electrode, and a sulfide solid electrolyte membrane formed by a wet process faces the negative electrode.

[0036] Wet-process solid electrolyte membranes are expensive, dry-process solid electrolyte membranes are prone to react with metallic lithium, sulfides are not resistant to high pressure, but are stable to lithium, and halides are resistant to high pressure, but unstable to metallic lithium. The present invention combines the advantages of the two solid electrolytes and the low-cost advantage of dry-wet composite solid electrolyte membrane technology to prepare a high-performance double-layer all-solid electrolyte membrane.

[0037] Compared with the prior art, the present invention proposes a new membrane making process, a dry-wet composite solid electrolyte membrane, using a low-cost halide solid electrolyte membrane prepared by a dry process as the main body, reducing the use of organic solvents and subsequent volatilization processes, reducing costs; then a wet sulfide solid electrolyte membrane is coated on one side of the dry halide solid electrolyte membrane, which faces the negative electrode, so that not only the PTFE commonly used on the dry side is easily reduced by metal lithium to appear "defluorination", low discharge capacity or self-discharge, but also the phenomenon of halide solid electrolyte being unstable to lithium is avoided. The dry halide solid electrolyte layer faces the positive electrode, giving play to the high-voltage resistance of the halide solid electrolyte and solving the problem of the narrow electrochemical window of the sulfide solid electrolyte. The dry-wet composite solid electrolyte membrane has low cost and low technical difficulty, and has the advantages of sulfide solid electrolyte and halide solid electrolyte at the same time, and abandons their respective shortcomings; it also concentrates the advantages of the dry process and the wet process, and is a new method for preparing a fully solid electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 :Process flow chart for preparation of dry-wet composite solid electrolyte membrane;

[0039] Figure 2 :Schematic diagram of the structure of dry-wet composite solid electrolyte membrane;

[0040] Figure 3 : Physical picture of battery testing equipment;

[0041] Figure 4 : First cycle charge and discharge curve of all-solid-state battery in Example 1;

[0042] Figure 5 : Comparative Examples 1 and 2: First cycle charge and discharge curves of all-solid-state batteries;

[0043] Figure 6 : Example 1, comparative example 2 all-solid-state battery cycle capacity test diagram. DETAILED DESCRIPTION

[0044] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0045] The ratios not specifically mentioned in the following examples refer to mass ratios.

[0046] Example 1

[0047] Figure 1 This is a process flow chart for preparing dry-wet composite solid electrolyte membranes. Figure 1 In this embodiment, a dry-wet composite solid electrolyte membrane is prepared, and the final result is as follows Figure 2 shown.

[0048] In an inert atmosphere, LZC (specifically Li2ZrCl6 in this embodiment) and PTFE are mixed in a mass ratio of 99.5:0.5, and the mixture is stirred, dispersed and fiberized using a high-speed planetary mixer ball mill. The ratio of zirconium beads to the mixture is controlled to be 15:1, the ball mill speed is set to 280 rpm, and the ball milling time is 1 h;

[0049] Under an inert atmosphere, the obtained LZC and PTFE mixture was placed in a first-level roller press for rolling at a pressure of 15t to obtain a solid electrolyte base membrane, which was then heated and rolled in a second-level roller press at a heating temperature of 90°C to form a dry solid electrolyte membrane with a thickness of 10um. It then entered a third-level roller press for compounding with a PET film at a pressure of 2t.

[0050] In an inert atmosphere, the solid electrolyte LPSC (specifically Li6PS5Cl in this embodiment) and PVDF are mixed in a ratio of 98:2 and added to isobutyl isobutyrate, with a solid content of 45wt%. The prepared solid electrolyte slurry is added to a coater, coated on a dry solid electrolyte membrane through a die head, and then placed in an oven for baking at 90°C, and finally placed in a 4-stage roller press for rolling at a pressure of 15t to obtain a dry-wet composite solid electrolyte membrane.

[0051] Example 2

[0052] Under an inert atmosphere, LZC (specifically Li2ZrCl6 in this embodiment) and PTFE are mixed in a ratio of 98.5:1.5, and the mixture is stirred, dispersed and fiberized using a high-speed planetary mixer ball mill, the ratio of zirconium beads to the mixture is controlled to be 15:1, the ball mill speed is set to 280 rpm, and the ball milling time is 1 h;

[0053] Under an inert atmosphere, the obtained LZC and PTFE mixture was placed in a first-level roller press for rolling at a pressure of 15t to obtain a solid electrolyte base membrane, which was then heated and rolled in a second-level roller press at a heating temperature of 90°C to form a dry solid electrolyte membrane with a thickness of 10um. It then entered a third-level roller press for compounding with a PET film at a pressure of 2t.

[0054] In an inert atmosphere, the solid electrolyte LPSC (specifically Li6PS5Cl in this embodiment) and PVDF are mixed in a ratio of 98:2 and added to isobutyl isobutyrate, with a solid content of 45wt%. The prepared solid electrolyte slurry is added to a coater, coated on a dry solid electrolyte membrane through a die head, and then placed in an oven for baking at 90°C, and finally placed in a 4-stage roller press for rolling at a pressure of 15t to obtain a dry-wet composite solid electrolyte membrane.

[0055] Example 3

[0056] In an inert atmosphere, LZC (specifically Li2ZrCl6 in this embodiment) and PTFE are mixed in a ratio of 99.5:0.5, and the mixture is stirred, dispersed and fiberized using a high-speed planetary mixer ball mill. The ratio of zirconium beads to the mixture is controlled to be 15:1, the ball mill speed is set to 280 rpm, and the ball milling time is 1 h;

[0057] Under an inert atmosphere, the obtained LZC and PTFE mixture was placed in a first-level roller press for rolling at a pressure of 15t to obtain a solid electrolyte base membrane, which was then heated and rolled in a second-level roller press at a heating temperature of 90°C to form a dry solid electrolyte membrane with a thickness of 30um. It then entered a third-level roller press for compounding with a PET film at a pressure of 2t.

[0058] In an inert atmosphere, the solid electrolyte LPSC (specifically Li6PS5Cl in this embodiment) and PVDF are mixed in a ratio of 98:2 and added to isobutyl isobutyrate, with a solid content of 45wt%. The prepared solid electrolyte slurry is added to a coater, coated on a dry solid electrolyte membrane through a die head, and then placed in an oven for baking at 90°C, and finally placed in a 4-stage roller press for rolling at a pressure of 15t to obtain a dry-wet composite solid electrolyte membrane.

[0059] Example 4

[0060] In an inert atmosphere, LZC (specifically Li2ZrCl6 in this embodiment) and PTFE are mixed in a ratio of 99.5:0.5, and the mixture is stirred, dispersed and fiberized using a high-speed planetary mixer ball mill. The ratio of zirconium beads to the mixture is controlled to be 15:1, the ball mill speed is set to 280 rpm, and the ball milling time is 1 h;

[0061] Under an inert atmosphere, the obtained LZC and PTFE mixture was placed in a first-level roller press for rolling at a pressure of 15t to obtain a solid electrolyte base membrane, which was then heated and rolled in a second-level roller press at a heating temperature of 90°C to form a dry solid electrolyte membrane with a thickness of 10um. It then entered a third-level roller press for compounding with a PET film at a pressure of 2t.

[0062] In an inert atmosphere, the solid electrolyte LPSC (specifically Li6PS5Cl in this embodiment) and PVDF are mixed in a ratio of 95:5 and added to isobutyl isobutyrate, with a solid content of 45wt%. The prepared solid electrolyte slurry is added to a coater, coated on a dry solid electrolyte membrane through a die head, and then placed in an oven for baking at 90°C, and finally placed in a 4-stage roller press for rolling at a pressure of 15t to obtain a dry-wet composite solid electrolyte membrane.

[0063] Example 5

[0064] In an inert atmosphere, LZC (specifically Li2ZrCl6 in this embodiment) and PTFE are mixed in a ratio of 99.5:0.5, and the mixture is stirred, dispersed and fiberized using a high-speed planetary mixer ball mill. The ratio of zirconium beads to the mixture is controlled to be 15:1, the ball mill speed is set to 280 rpm, and the ball milling time is 1 h;

[0065] Under an inert atmosphere, the obtained LZC and PTFE mixture was placed in a first-level roller press for rolling at a pressure of 15t to obtain a solid electrolyte base membrane, which was then heated and rolled in a second-level roller press at a heating temperature of 90°C to form a dry solid electrolyte membrane with a thickness of 10um. It then entered a third-level roller press for compounding with a PET film at a pressure of 2t.

[0066] In an inert atmosphere, the solid electrolyte LPSC (specifically Li6PS5Cl in this embodiment) and PVDF are mixed in a ratio of 98:2 and added to isobutyl isobutyrate, with a solid content of 45wt%. The prepared solid electrolyte slurry is added to a coater, coated on a dry solid electrolyte membrane through a die head, and then placed in an oven for baking at 90°C, and finally placed in a 4-stage roller press for rolling at a pressure of 5t to obtain a dry-wet composite solid electrolyte membrane.

[0067] Comparative Example 1

[0068] In an inert atmosphere, solid electrolyte LZC (specifically Li2ZrCl6 in this comparative example) and PVDF were mixed in a ratio of 98:2 and added to isobutyl isobutyrate, with a solid content of 45wt%. The prepared solid electrolyte slurry was added to a coating machine, coated on a PET film through a die head, and then placed in an oven for baking at a temperature of 90°C to obtain a wet solid electrolyte membrane.

[0069] In an inert atmosphere, the solid electrolyte LPSC (specifically Li6PS5Cl in this comparative example) and PVDF were mixed in a ratio of 98:2 and added to isobutyl isobutyrate, with a solid content of 45wt%. The prepared solid electrolyte slurry was added to a coater, coated on a wet solid electrolyte membrane through a die head, and then placed in an oven for baking at 90°C, and finally placed in a 4-stage roller press for rolling at a pressure of 15t to obtain a wet composite solid electrolyte membrane.

[0070] Comparative Example 2

[0071] In an inert atmosphere, LZC (specifically Li2ZrCl6 in this comparative example) and PTFE were mixed in a ratio of 99.5:0.5, and the mixture was stirred, dispersed and fiberized using a high-speed planetary mixer ball mill. The ratio of zirconium beads to the mixture was controlled to be 15:1, the ball mill speed was set to 280 rpm, and the ball milling time was 1 h.

[0072] Under an inert atmosphere, the obtained LZC and PTFE mixture was placed in a first-level roller press for rolling at a pressure of 15t to obtain a solid electrolyte base membrane, which was then heated and rolled by a second-level roller press at a heating temperature of 90°C to obtain a dry solid electrolyte membrane 1 with a thickness of 10um. It then entered a third-level roller press for compounding with a PET film at a pressure of 2t.

[0073] Under an inert atmosphere, LPSC (specifically Li6PS5Cl in this comparative example) and PTFE were mixed in a ratio of 99.5:0.5, and the mixture was stirred, dispersed and fiberized using a high-speed planetary mixer ball mill. The ratio of zirconium beads to the mixture was controlled to be 15:1, the ball mill speed was set to 280 rpm, and the ball milling time was 1 h.

[0074] Under an inert atmosphere, the obtained LPSC and PTFE mixture was placed in a first-stage roller press for rolling at a pressure of 15t to obtain a solid electrolyte base membrane, which was then heated and rolled at a temperature of 90°C in a second-stage roller press to obtain a dry solid electrolyte membrane 2 with a thickness of 10um. It then entered a third-stage roller press for compounding with a PET film at a pressure of 2t.

[0075] The dry solid electrolyte membrane 1 and the dry solid electrolyte membrane 2 are compounded and put into a three-stage roller press for rolling at a pressure of 2 tons to obtain a compound dry solid electrolyte membrane.

[0076] Comparative Example 3

[0077] Under an inert atmosphere, LPSC (specifically Li6PS5Cl in this comparative example) and PTFE were mixed in a ratio of 99.5:0.5, and the mixture was stirred, dispersed and fiberized using a high-speed planetary mixer ball mill. The ratio of zirconium beads to the mixture was controlled to be 15:1, the ball mill speed was set to 280 rpm, and the ball milling time was 1 h.

[0078] Under an inert atmosphere, the obtained LPSC (specifically Li6PS5Cl in this comparative example) and PTFE mixture were placed in a first-stage roller press for rolling at a pressure of 15t to obtain a solid electrolyte base membrane, which was then heated and rolled by a second-stage roller press at a heating temperature of 90°C to obtain a dry solid electrolyte membrane with a thickness of 10um. It then entered a third-stage roller press for compounding with a PET film at a pressure of 2t.

[0079] Comparative Example 4

[0080] In an inert atmosphere, the solid electrolyte LPSC (specifically Li6PS5Cl in this comparative example) and PVDF were mixed in a ratio of 98:2 and added to isobutyl isobutyrate, with a solid content of 45wt%. The prepared solid electrolyte slurry was added to a coating machine, coated on a PET film through a die head, and then placed in an oven for baking at a temperature of 90°C to obtain a wet solid electrolyte membrane.

[0081] The dry-wet composite solid electrolyte membranes prepared in the above Examples 1-5 and the electrolyte membranes prepared in Comparative Examples 1-4 were cut into discs with a diameter of 13 mm and placed in a mold battery. A certain pressure of 450 MPa / cm was given to the mold battery. 2 The actual picture of battery testing equipment is as follows Figure 3 As shown, the device includes a pressurizing device, an upper screw, a lower screw, a sleeve, a wire and an electrochemical workstation. The pressurizing device can apply a constant pressure to the upper screw and the lower screw. The upper end of the upper screw is connected to a conductive terminal, and the lower end of the lower screw is connected to a conductive terminal. The top surfaces of the upper and lower screws are flat and the same size. The diameter of the hollowed-out part in the middle of the sleeve is consistent with that of the upper and lower screws. The wire connects the terminal of the upper screw and the electrochemical workstation, and connects the terminal of the lower screw and the electrochemical workstation. The ionic conductivity at room temperature is determined by the AC impedance method. The measurement results of lithium ion conductivity at 25°C are shown in Table 1:

[0082] Table 1 Lithium ion conductivity under solid electrolyte membrane based on different embodiments and comparative examples

[0083]

[0084]

[0085] The dry-wet composite solid electrolyte membrane obtained by coating the wet solid electrolyte layer in Example 1 with different thicknesses was tested for lithium ion conductivity at 25°C, and the results are shown in Table 2:

[0086] Table 2 Lithium ion conductivity under solid electrolyte membrane of different thicknesses based on Example 1

[0087]

[0088] It can be seen that with the increase of the thickness of the wet solid electrolyte layer, the ionic conductivity of the dry-wet composite solid electrolyte membrane shows a trend of first increasing and then decreasing, which is related to which solid electrolyte layer, the dry or wet, is dominant in the dry-wet composite solid electrolyte membrane.

[0089] Figure 4 The first cycle charge and discharge curve of the all-solid-state battery assembled with the dry-wet composite solid electrolyte membrane prepared in Example 1. The positive electrode uses Ni90 ternary nickel-cobalt-manganese material / sulfide electrolyte / vapor-grown carbon fiber composite material, the negative electrode is metallic lithium, and the mold battery is assembled at a pressure of 450Mpa / cm 2 The test temperature is 25℃. The first cycle charge capacity at 0.1C is 242.4mAh g -1 , the discharge capacity is 189.8 mAh g -1 , the first-cycle Coulomb efficiency is 78.28%.

[0090] Figure 5 The first cycle charge and discharge curves of the all-solid-state battery assembled with the dry composite solid electrolyte membrane prepared in Comparative Examples 1 and 2, the positive electrode uses Ni90 ternary nickel-cobalt-manganese material / sulfide electrolyte / vapor-grown carbon fiber composite material, the negative electrode is metallic lithium, and the battery is assembled using a mold, the pressure is 450Mpa / cm2. The test temperature is 25°C. The first cycle charge capacity of the all-solid-state battery assembled with the dry composite solid electrolyte membrane is 248.6mAh g -1 , the discharge capacity is 143.3 mAh g -1 The first cycle coulombic efficiency is 57.64%. The first cycle charge capacity of the all-solid-state battery assembled by wet composite solid electrolyte membrane is 243.1mAh g -1 , the discharge capacity is 196.9 mAh g -1 , the first-cycle Coulomb efficiency is 81.01%.

[0091] Figure 6The test graph of the cycle capacity of the all-solid-state battery assembled with the dry-wet composite solid electrolyte membrane prepared in Example 1 and the dry-composite solid electrolyte membrane of Comparative Example 2. The positive electrode uses Ni90 ternary nickel-cobalt-manganese material / sulfide electrolyte / vapor-grown carbon fiber composite material, the negative electrode is metallic lithium, and the mold battery is assembled at a pressure of 450Mpa / cm 2 The test temperature was 25°C. The capacity retention rate of the battery assembled with the dry-wet composite solid electrolyte membrane of Example 1 after 60 cycles was 85.19%, and the capacity retention rate of the battery assembled with the dry-composite solid electrolyte membrane of Comparative Example 2 after 60 cycles was 73.80%.

[0092] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a double-layer all-solid electrolyte membrane, characterized in that: The following steps are involved: 1) preparing a first solid electrolyte membrane on a substrate by a dry process; 2) A wet process is used to coat a second solid electrolyte slurry on one side of the first solid electrolyte membrane, dry it, and roll-press it to obtain a double-layer all-solid electrolyte membrane.

2. The method for preparing a double-layer all-solid electrolyte membrane according to claim 1, characterized in that: The method for preparing the first solid electrolyte membrane on the substrate by using a dry process is as follows: The first solid electrolyte powder and the binder are fiberized, and the fiberized mixture is rolled into a base film by a first-stage roller press, and then heated and rolled to a target thickness by a second-stage roller press to obtain a first solid electrolyte membrane, and then the first solid electrolyte membrane is attached to the substrate by a third-stage roller press so that it has a certain tensile strength in subsequent processes.

3. The method for preparing a double-layer all-solid electrolyte membrane according to claim 2, characterized in that: The mass ratio of the first solid electrolyte powder to the binder is 95:5 to 99.9:0.1; The first solid electrolyte is selected from a sulfide solid electrolyte, a halide solid electrolyte or an oxide solid electrolyte, preferably a halide solid electrolyte; The binder is selected from any one or more combinations of PTFE, cellulose mesh, nylon mesh or Kevlar mesh; The fiberization treatment is carried out by using a combination of one or more of a high-speed planetary mixer, a three-dimensional mixer or a drum mixer; The heating temperature of the two-stage roller press is 45°C-130°C.

4. The method for preparing a double-layer all-solid electrolyte membrane according to claim 3, characterized in that: The thickness of the first solid electrolyte membrane is 5um-45um.

5. The method for preparing a double-layer all-solid electrolyte membrane according to claim 1, characterized in that: The specific method of using a wet process to coat a second solid electrolyte slurry on one side of a first solid electrolyte membrane, drying, and rolling to obtain a double-layer all-solid electrolyte membrane is as follows: A second solid electrolyte slurry is prepared, and the second solid electrolyte and a binder are added to a low-polarity solvent, stirred and dispersed, and the prepared second solid electrolyte slurry is coated on the first solid electrolyte membrane through a die head, and after baking, it is rolled and compounded by a 4-stage roller press to finally obtain a dry-wet composite solid electrolyte membrane, that is, a double-layer all-solid-state electrolyte membrane.

6. The method for preparing a double-layer all-solid electrolyte membrane according to claim 5, characterized in that: The mass ratio of the second solid electrolyte to the binder is 90:10 to 99.5:0.5; The second solid electrolyte is selected from a sulfide solid electrolyte, a halide solid electrolyte or an oxide solid electrolyte, preferably a sulfide solid electrolyte; The binder is selected from one or more of PVDF, nitrile rubber, polyvinylidene fluoride, butadiene rubber, polyvinyl alcohol butyral, styrene ethylene butylene styrene copolymer, hydrogenated nitrile rubber, polyisobutylene, carboxymethyl cellulose, ethyl cellulose or polyvinyl acetate; The low polarity solvent is selected from one or more of isobutyl isobutyrate, toluene, xylene, chlorobenzene, n-hexane, cyclohexane, heptane, ethyl propionate, dimethyl carbonate or dibutyl ether; The baking temperature is 45°C-130°C; The pressure of the 4-stage roller press is 5t-30t.

7. The method for preparing a double-layer all-solid electrolyte membrane according to claim 1, characterized in that: A method for preparing a double-layer all-solid electrolyte membrane comprises the following steps: 1) A halide solid electrolyte membrane is prepared on a substrate using a dry process; 2) A wet-blowing process is used to coat a sulfide solid electrolyte slurry on one side of the halide solid electrolyte membrane, which is then dried and rolled to obtain a double-layer all-solid electrolyte membrane.

8. A double-layer all-solid electrolyte membrane prepared by the method according to any one of claims 1 to 7, characterized in that: comprising a substrate, a first solid electrolyte layer formed on the substrate, and a second solid electrolyte layer formed on the first solid electrolyte layer; In the double-layer all-solid-state electrolyte membrane, the first solid-state electrolyte layer is selected as a halide solid-state electrolyte layer, and the second solid-state electrolyte layer is selected as a sulfide solid-state electrolyte layer.

9. Use of the double-layer all-solid-state electrolyte membrane according to claim 8 in the preparation of solid-state batteries.

10. A solid-state battery, characterized in that: Containing the double-layer all-solid electrolyte membrane as claimed in claim 8.

Citation Information

Cited By

  • Double-layer electrolyte transfer printing preparation method for optimizing positive and negative electrode interfaces of all-solid-state battery and all-solid-state battery

    CN120511357A